Evaluasi kinerja saluran drainase Kelurahan Drangong, Kecamatan Taktakan menggunakan SWMM 5.2 - Alfan Qashdus Sabil; Muhammad Oka Mahendra; Hadi Wiguno (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
This study aims to evaluate the performance of the drainage system in Drangong Subdistrict, Taktakan District, using SWMM 5.2 software with a focus on peak discharge and overflow points, which frequently cause flooding due to inadequate channel capacity, sedimentation, and blockages. The analysis employed the EPA Storm Water Management Model version 5.2 to quantitatively assess the existing drainage system, utilizing primary data from field surveys (channel dimension measurements and sedimentation levels) and secondary data, including daily rainfall records for ten years (2015–2024) from the BMKG Serang Climatology Station and a 1:10,000 scale topographic map of Drangong Subdistrict. Hydrological analysis was conducted using the Log Pearson Type III distribution to determine design rainfall for return periods of 2, 5, 10, and 25 years, while peak discharge was calculated using the Rational Method. The SWMM simulation identified potential overflow points and revealed the inability of the existing drainage system to accommodate the design discharge, particularly for the 25-year return period with rainfall intensity of 131.04 mm/hour and peak discharge of 2.183 m³/second. The findings indicate that the current drainage capacity remains sufficient for 2-, 5-, and 10-year return periods but is inadequate for the 25-year return period. This study recommends improvements to channel dimensions, hydraulic capacity, and sedimentation and waste management to optimize the drainage system in the study area.